Natural and divine law reclaiming the tradition for Christian ethics - Porter, Jean, 1955- (Ottawa, ON Novalis, 1999)
Includes bibliographical references and indexes.
Keywords: Natural law -- history; Scolasticism -- history; Christian ethics